Treatment Outcomes and Perception of Social Acknowledgment in War Veterans: Follow-up Study - Ljubotina, Damir (Array, 2007)
Aim was to assess treatment outcomes of psychotherapy for war veterans suffering from posttraumatic stress disorder (PTSD) and to investigate selfperceived social acknowledgment. In this prospective cohort study, a set of psychological instruments was used to assess the level of posttraumatic stress symptoms (Clinician- Administered PTSD Scale, Impact of Event Scale – Revised), symptoms of general psychopathology (Brief Symptom Inventory), quality of life (The Manchester Short Assessment of Quality of Life), and perceived social acknowledgment on a sample of 152 Croatian war veterans participating in group psychotherapy. All participants were interviewed at baseline and followed up after 3 and 12 months. We analyzed the changes in symptom levels over the course of one year, as well as the correlations between symptoms (both at baseline and after therapy) and perceived social acknowledgment. The analysis of symptom levels at the beginning of group therapy and after 12 months showed minimal or no changes in their intensity. Only the symptoms of intrusion (ANOVA, F-value = 7.09, P<0.001) were significantly reduced after a period of 12 months. Levels of hostility (ANOVA, F-value = 7.85, P<0.001) and psychoticism were significantly increased (ANOVA, F-value = 7.80, P<0.001) at the end of the treatment. Other categories of posttraumatic symptoms and the level of general psychopathology did not change significantly during the course of treatment. The results showed that war veterans perceive extremely low levels of social acknowledgment, especially from their wider social environment: 92.9% perceived a lack of acknowledgment from governmental institutions and 95.4% from the state in general. Despite some methodological constraints, our results showed that even 10 years after the traumatization, PTSD symptoms among war veterans remained intense and that undergoing therapy over a year did not produce significant improvements, except on the dimension of intrusion. Veterans were highly sensitive to the way their primary social environment and the society as a whole react to their problems.